Toward a greener globe : In the pursuit of culturally embedded pathways to sustainable consumption - Rahman, Saleem ur (Vaasan yliopisto, 2019)
Consumers may enjoy the pleasure of preventing environmental degradation by purchasing environmentally friendly products. However, sustainable consumption is complex type of decision-making, and “greening” the consumption patterns of consumers is not straightforward. There are many motives that consumers may have for buying environmentally friendly products. In view of that, this dissertation examines individual vs collective culturally congruent motives for sustainable consumption. The first essay of this dissertation examines the role of horizontal and vertical individualism vs collectivism cultural values (H/V IND-COL) in the relationship between green branding and consumers’ green behavioral intentions (e.g. word-of-mouth intentions, the willingness to pay a premium, and purchase intentions). Consumers’ intentions to purchase green products differ with respect to their cultural backgrounds. The second essay explores how H/V IND-COL cultural values are reflected in consumers’ organic food choice motivations and product perceptions when viewed through the lens of life goals. Consumers’ cultural values and life goals both converge and diverge regarding their organic food-product choices. The third essay examines the role of regulatory focus as a personal motivational construct in determining consumers’ sustainable product-consumption experience in H/V IND-COL cultures. This third essay demonstrates that H/V IND-COL values influence consumers’ prevention-focused and promotion-focused environmental behavior. The fourth essay examines if environmental responsibility as a personal motivational construct mediates the effects of H/V IND-COL cultural values on consumers’ environmental attitudes and purchase intentions. Environmental responsibility not only influences consumers’ environmental behavior but also plays a mediating role between H/V IND-COL cultural values and environmental behavior. The findings of this dissertation contribute to existing research on cross-cultural sustainable consumption, specifically to the research examining individual vs collective cultural motives of sustainable consumption. The results indicate significant differences between consumers’ sustainable consumption choices in countries whose cultures could be broadly described as “individualistic” and “collectivistic.” The results of this dissertation have the potential to help companies tailor culturally congruent green marketing and advertising strategies.

Ostaessaan ympäristöystävällisiä tuotteita kuluttajat voivat kokea mielihyvää voidessaan vaikuttaa ympäristön pilaantumisen torjumiseen. Kestävä kulutus on kuitenkin luonteeltaan monimutkaista päätöksentekoa ja kuluttajien kulutusmallien "vihertyminen" ei ole suoraviivaista. Kuluttajilla voi olla useita motiiveja ostaessaan ympäristöystävällisiä tuotteita. Tämä huomioiden esillä oleva väitöskirja tarkastelee individualistiseen vs. kollektiiviseen kulttuuriin pohjautuvia kestävän kulutuksen motiiveja. Väitöskirjan ensimmäinen essee kohdistuu horisontaalisen ja vertikaalisen individualistisen kulttuurin arvoihin vs. kollektiivisen kulttuurin arvoihin (lyhennettynä H/V IND-COL) tuotteiden vihreän brändäämisen ja kuluttajien vihreiden kulutusaikomusten suhteen (suusanallinen viestintä, ostaminen, lisähinnan maksaminen). Kuluttajien vihreiden tuotteiden ostoaikomukset eroavat kulttuuritaustan myötä. Toinen essee tarkastelee sitä, kuinka H/V IND-COL -kulttuurin arvot heijastuvat kuluttajien luomuruoan valintamotiiveihin ja tuotekokemuksiin tarkasteltuna elämää ohjaavien peruspäämäärien näkökulmasta. Kuluttajien kulttuuriperusteiset arvot ja elämän peruspäämäärät sekä yhdentyvät että eriytyvät luomuruokatuotteiden valinnoissa. Kolmannessa esseessä tutkitaan itsesäätelyn kohdentumisen (regulatory focus) roolia henkilökohtaisena motiivirakenteena, kun määritetään kuluttajien kestävää tuote-kulutuskokemusta H/V IND-COL -kulttuureissa. Kolmas essee osoittaa, että H/V IND-COL -arvot vaikuttavat kuluttajien välttämis- ja lähestymislähtöiseen ympäristöä koskevaan käyttäytymiseen. Neljäs essee tarkastelee, onko ympäristövastuun kokemisella henkilökohtaisena motiivirakenteena merkitystä siihen, kuinka H/V IND-COL -kulttuurin arvot vaikuttavat kuluttajien ympäristöasenteisiin ja ostoaikomuksiin. Koettu ympäristövastuu ei vain vaikuta kuluttajien ympäristöä koskevaan käyttäytymiseen, vaan toimii myös säätelevässä roolissa H/V IND-COL- ja ympäristöllisen käyttäytymisen välisessä suhteessa. Tämän väitöskirjan tulokset tuovat oman osuuteensa monikulttuurista kestävää kuluttamista koskevaan tutkimukseen, erityisesti koskien tutkimusta individualistisen vs. kollektiivisen kulttuuriin nojaavista kestävän kulutuksen motiiveista. Tulokset osoittavat merkittäviä eroja kestävissä kulutusvalinnoissa niissä maissa, joiden kulttuuria voidaan laajasti kuvata "individualistiseksi" ja "kollektiiviseksi". Tämän väitöskirjan tulokset voivat auttaa yrityksiä räätälöimään kulttuurin huomioivaa vihreää markkinointia ja mainontaa koskevia strategioita.
Kohti vihreämpää maailmaa : kulttuurierojen ymmärtäminen kestävän kulutuksen edistämisen väylänä
Keywords: Culture; Consumers; Horizontal; Vertical; Individualism; Collectivism; Regulatory focus; Environmental responsibility; Sustainable consumption; kestävä kulutus; ympäristöystävälliset tuotteet; ympäristöasenteet; kuluttajat; kuluttajakäyttäytyminen; ympäristövastuu; fi=Markkinointi|en=Marketing|